Preferensi Wereng Batang Cokelat terhadap Varietas Padi dan Ketahanan Varietas Padi terhadap Virus Kerdil Hampa - Suprihanto, Suprihanto; Somowiyarjo, Susamto; Hartono, Sedyo; Trisyono, Y. Andi (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Rice ragged stunt virus (RRSV) is transmitted by brown planthopper in the persistent manner. This disease in recent years has become a serious problem in Indonesia and some other countries, such as China, Vietnam, Philippines, and Thailand. Disease control is usually conducted by the vector control using insecticides, so often causes an environmental pollution. An alternative control method is using the environmentally friendly of resistant varieties. The purpose of this study was to determine the level of preference of brown planthopper (BPH) to some varieties and rice germplasms, the resistance of several varieties against rice ragged stunt virus (RRSV) disease and its effectiveness as an inoculum source of virus (RRSV). A total of 15 varieties of rice were used in preference test of BPH and resistance test to RRSV. The test for resistance varieties to RRSV was conducted by transmission of 2nd instar of BPH for 3 days of acquisition feeding period, 10 days incubation period and 24 hours inoculation period with population density of 3 BPH/plant. Disease index was calculated and used to determine the level of plant resistance. Varieties that showed resistant, moderately resistant and susceptible responses were selected and were used as a source of inoculum to be transmitted on to TN1 variety susceptible check variety to know the effectiveness of varieties as source of virus inoculum. The results showed that of the 15 varieties tested, Situ Bagendit, Utri Merah, Mentik Wangi, Mahsuri, and Inpari 1 each was less favored by BPH to settle and to multiply. Mentik Wangi, Tetep, Utri Merah, and Swarnalata each showed resistant response to RRSV. Transmission test to susceptible variety (TN1) showed that the variety of Situ Bagendit, Inpari 13, Mentik Wangi, and Tetep each has a fairly low effectiveness as a source of inoculum as indicated by the lower percentage of infection and disease index on the transmited test plants.